PERAN KOMUNIKASI ORGANISASI PERKUMPULAN MASYARAKAT SURAKARTA (PMS) DALAM MENJAGA EKSISTENSI WARGA KETURUNAN TIONGHOA DI WILAYAH KOTA MADYA SURAKARTA - Duta Arya (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2020)
This study aims to see how the role of organization communication maintaining the existence of a community groups. Surakarta people association is able to maintain its existence and indirectly also give a big contribution in maintaining the existence of Chinese descent who are under the this association.The approach of this research is qualitative method that is expected to be able to answer thoroughly and deeply from the subject matter and get the of research problem. By using qualitative methods, the obtained data will be more depth and suitable with the phenomenon of this study. The qualitative approach conducted with interview and discussion techniques it is expected to the results of this study can describe the whole subject matter of the study.This study shows the role of organizational communication can maintain the existence of Chinese descendants groups in the Surakarta region, the role of organizational communication run by the leaders of organization is acceptable to the board and members of Surakarta people association it makes the organization is able to carry out activities in their respective fields that show the existence of Chinese descent in the Surakarta region, by the implementation of activities in the field of sports, education, health, social, can run well and sustainable, so its existence is recognized not only by the local government but also all community lines in Surakarta and surrounding areas.